Application of new balloon catheters in the treatment of congenital heart defects - Fiszer, Roland; Szkutnik, Małgorzata; Litwin, Linda; Smerdziński, Sebastian; Chodór, Beata; Białkowski, Jacek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : Balloon angioplasty (BAP) and aortic or pulmonary balloon valvuloplasty (BAV, BPV) are well-established treatment options in congenital heart defects. Recently, significant technological progress has been made and new catheters have been implemented in clinical practice. Aim: To analyze the results of BAP, BAV and BPV with the new balloon catheter Valver and its second generation Valver II, which the company Balton (Poland) launched and developed. These catheters have not been clinically evaluated yet. Material and methods: We performed 64 interventions with Valver I and Valver II. With Valver I the following procedures were performed: 17 BPV (including 9 in tetralogy of Fallot – TOF), 10 BAV and 27 BAP in coarctations of the aorta (CoA) – including 9 native and 18 after surgery. With Valver II ten interventions were done – 3 BPV, 2 pulmonary supravalvular BAP (after switch operations), 2 BAP of recoarctations and 3 other BAP. Age of the patients ranged from a few days to 40 years. Results: All procedures were completed successfully, without rupture of any balloon catheters. The pressure gradient drop was statistically significant in all groups: BPV in isolated pulmonary valvular stenosis 28.1 mm Hg (mean), BPV in TOF 18.7 mm Hg, BAV 32.8 mm Hg, BAP in native CoA 15.4 mm Hg and in recoarctations 18.6 mm Hg. In 3 cases during rapid deflation of Valver I, wrinkles of the balloons made it impossible to insert the whole balloon into the vascular sheath (all were removed surgically from the groin). No such complication occured with Valver II. Conclusions : Valver balloon catheters are an effective treatment modality in different valvular and vascular stenoses.